The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.bmcl.2016.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological protection of mitochondrial function mitigates acute limb ischemia/reperfusion injury

Abstract: We describe several novel curcumin analogues that possess both anti-inflammatory antioxidant properties and thrombolytic activities. The therapeutic efficacy of these curcumin analogues was verified in a mouse ear edema model, a rat arterial thrombosis assay, a free radical scavenging assay performed in PC12 cells, and in both in vitro and in vivo ischemia/reperfusion models. Our findings suggest that their protective effects partially reside in maintenance of optimal mitochondrial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In our analyses, human umbilical vein endothelial (HUVEC) cells were subjected to simulated I/R injury employing a flow-through process. 31,32 During simulated ischemia, no significant cell death was observed. After exposure of cells to simulated ischemia followed by 3h of reperfusion, cell death exceeded 80%.…”
Section: Protective Effect Of Indole-tempo Conjugates In a Simulated mentioning
confidence: 93%
See 1 more Smart Citation
“…In our analyses, human umbilical vein endothelial (HUVEC) cells were subjected to simulated I/R injury employing a flow-through process. 31,32 During simulated ischemia, no significant cell death was observed. After exposure of cells to simulated ischemia followed by 3h of reperfusion, cell death exceeded 80%.…”
Section: Protective Effect Of Indole-tempo Conjugates In a Simulated mentioning
confidence: 93%
“…The HOMO energy, which characterizes the ability of electrondonation, is appropriate to represent the free radical scavenging efficiency of nitroxides because the process to inhibit autooxidation may include the electron-transfer in combination with the abstraction of the H-atom. [31][32][33] A higher HOMO energy implies that the molecule is a better electron donor. Because the abstraction of hydrogen involves electron transfer, the HOMO composition of a nitroxide can provide qualitative insights into the identity of its active site for the scavenging radical activity.…”
Section: Molecular Dynamic Simulation Studiesmentioning
confidence: 99%
“…Moreover, they exhibited strong DPPH scavenging ability, which was about 10 times stronger than that of curcumin and has good antiproliferative activity on a variety of cancer cells, with an IC 50 value of <1 μM. Furthermore, Bi et al ( 2016 ) got a new class of derivatives that can associate apoptosis induced by ischemia/reperfusion injury and reverse mitochondrial oxidative stress. The results suggest that selected curcumin polypeptide analogs 57 (EC 50/.OH = 25.6 μM) and 58 (EC 50/.OH = 31.4 μM) exhibited good hydroxyl radical scavenging activity and can facilitate the recovery of mitochondrial reticular networks and cell rescue ( Figure 7B ).…”
Section: Application Of Amino Acids In the Structural Modification Of Natural Productsmentioning
confidence: 99%
“…Researchers have reported that antioxidants such as vitamin E, l -arginine, curcumin, and mitochondrion-targeted peptide protect skeletal muscle against I/R injury. 11 14…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that antioxidants such as vitamin E, L-arginine, curcumin, and mitochondrion-targeted peptide protect skeletal muscle against I/R injury. [11][12][13][14] Our previous study showed that edaravone (3-methy-1-pheny1-2-pyrazolin-5-one), a potent systemic scavenger of free radicals, protects the hind limb skeletal muscles of mice against I/R injury induced by application of a tourniquet for 1.5 h. 15 Edaravone inhibits both nonenzymatic lipid peroxidation and the lipoxygenase pathway, in addition to exhibiting potent antioxidant effects against I/R injury-induced vascular endothelial cell injury, delayed neuronal death, brain edema, and concomitant neurologic deficits. Edaravone was approved for use in treating acute brain infarctions in Japan in 2002; in 2015, it was approved for treating amyotrophic lateral sclerosis based on its neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%